Indwelling tunneled pleural catheters for refractory hepatic hydrothorax in patients with cirrhosis: a multicenter study - Shojaee, S; Rahman, N; Haas, K; Kern, R; Leise, M; Alnijoumi, M; Lamb, C; Majid, A; Akulian, J; Maldonado, F; Lee, H; Khalid, M; et al. (Elsevier, 2018)
Background: The outcome of indwelling pleural catheter (IPC) use in hepatic hydrothorax (HH) is unclear. This study aimed to review the safety and feasibility of the IPC in patients with refractory HH. Methods: A retrospective multicenter study of patients with HH from January 2010 to December 2016 was performed. Inclusion criteria were refractory HH treated with an IPC and an underlying diagnosis of cirrhosis. Records were reviewed for patient demographics, operative reports, and laboratory values. The Kaplan-Meier method was used to estimate catheter time to removal. The Cox proportional hazard model was used to evaluate for independent predictors of pleurodesis and death. Results: Seventy-nine patients were identified from eight institutions. Indication for IPC placement was palliation in 58 patients (73%) and bridge to transplant in 21 patients (27%). The median in situ dwell time of all catheters was 156 days (range, 16-1,978 days). Eight patients (10%) were found to have pleural space infection, five of whom also had catheter-site cellulitis. Two patients (2.5%) died secondary to catheter-related sepsis. Catheter removal secondary to spontaneous pleurodesis was achieved in 22 patients (28%). Median time from catheter insertion to pleurodesis was 55 days (range, 10-370 days). Older age was an independent predictor of mortality on multivariate analysis (hazard ratio, 1.05; P = .01). Conclusions: We present, to our knowledge, the first multicenter study examining outcomes related to IPC use in HH. Ten percent infection risk and 2.5% mortality were identified. IPC placement may be a reasonable clinical option for patients with refractory HH, but it is associated with significant adverse events in this morbid population.